1983
DOI: 10.1056/nejm198308043090505
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of Hyperprolactinemia after Selective Transsphenoidal Adenomectomy in Women with Prolactinoma

Abstract: To assess the long-term prognosis for women with prolactinoma after selective transsphenoidal adenomectomy, we followed 44 patients for 6.2 +/- 1.5 years. Group 1 (28 patients) had microprolactinomas, and Group 2 (16 patients) had macroprolactinomas. After surgery, normal plasma prolactin levels, resumption of menses, and cessation of galactorrhea were observed in 24 Group 1 patients (85 per cent) and 5 Group 2 patients (31 per cent). Hyperprolactinemia recurred in 12 of the 24 Group 1 patients and in 4 of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
63
2
6

Year Published

1984
1984
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(79 citation statements)
references
References 13 publications
5
63
2
6
Order By: Relevance
“…In our study, about 34% of patients with postoperative remission relapsed 7-164 months after initial surgery, a recurrence rate higher than those reported in recent studies (17,18,19,20,21) but similar to findings from older publications with long follow-up periods of up to 148 months (29,30,31,32). Noticeably, recurrence of hyperprolactinemia seems to occur at a constant rate over time and half of the relapsing patients did so 3 years or more after surgery.…”
Section: Discussionsupporting
confidence: 87%
“…In our study, about 34% of patients with postoperative remission relapsed 7-164 months after initial surgery, a recurrence rate higher than those reported in recent studies (17,18,19,20,21) but similar to findings from older publications with long follow-up periods of up to 148 months (29,30,31,32). Noticeably, recurrence of hyperprolactinemia seems to occur at a constant rate over time and half of the relapsing patients did so 3 years or more after surgery.…”
Section: Discussionsupporting
confidence: 87%
“…32,38 The recurrence rate is also greater (as high as 80%). 32,41 Based on this series, it is our finding that in difficult cases GKS can induce a remission in an additional 11% of patients off medication.…”
Section: Role Of Gks In Multimodal Therapymentioning
confidence: 67%
“…32,38 In patients with microprolactinomas, the lesion recurs in 17 to 50%. 32,41 In patients with macroprolactinomas surgical remission is less successful, occurring in 28 to 53% of patients. 32,38 The recurrence rate is also greater (as high as 80%).…”
Section: Role Of Gks In Multimodal Therapymentioning
confidence: 99%
“…The success rates are highly variable ranging from 6.7 to 80% and recurrence rate being 7-50%. 10, 11 Maiter D et al in 2014 reviewed the management of giant prolactinoma cases and found that the extensive tumours are usually not completely resectable and neurosurgery has significant morbidity and mortality. 12 So additional therapy after operation using conventional external radiation may be needed, but it takes several years to achieve endocrinological remission and risk for panhypopituitarism or visual disturbances exists.…”
Section: Discussionmentioning
confidence: 99%